Accessibility and usability of commercial services for disabled people in poland and in the eu and efta countries - MirosÅ‚aw GrewiÅ„ski; Karolina Geletta (European Journal of Bioethics, 2014)
The purpose of this report is to identify the best solutions to Europeâ€™s accessibility andÂ usability of commercial services for people with disabilities in the European Union andÂ EFTA. In conjunction with the previous report â€“ â€œThe impact of the community of peopleÂ with disabilities on the socio-economic position in selected countries of the EU and EEAÂ accessibility and usability of public services in the areas of education, employment andÂ counseling, various forms of health care and rehabilitationâ€ - provides a comprehensive lookÂ at solutions for the delivery of services to disabled people in the EU / EFTA countries. In theÂ writing section on commercial services, much less widespread in the EU in relation to publicÂ services, the authors tried to choose the solutions belong to the domain. â€œBest practicesâ€Â that are worth considering the possible implementation in Poland. Commercial services haveÂ significantly less widespread in the EU in relation to public services in the writing section,Â so the authors tried to choose the solutions belong to the domain: â€œBest practicesâ€ that areÂ worth considering for the possible implementation in Poland. Commercial service market isÂ the most developed in countries of Weberâ€™s â€œProtestant ethicâ€; commercial services are stillÂ only residually in many EU countries, this is often due to historical reasons, and attachmentÂ to this, but not to other model of the welfare state. The first part of the report presents the solutions for the commercial housing services andÂ related supporting services such as health and respite care. As the most interestingÂ commercial solutions on the EU market the authors found the Dutch housing clusters whichÂ are a model example of the use of architecture to the needs of people with disabilities. AnÂ important fact is their wide dissemination. More than 1300 houses covers practically all of theÂ Netherlands. As a second example of commercial housing services is shown in the UK, alongÂ with a model â€œsupported livingâ€ where service innovation is separated from the residentialÂ care services, in order to promote the ideal independent life for the disabled people. In the second part of the report the authors present situation regarding the care andÂ rehabilitation services, and other support services. The most interesting current trend inÂ Western Europe seems to be the idea of â€œdirect depositâ€ and â€œpersonal budgetsâ€. The authorsÂ present three completely different models of personal budgets used in the UK, GermanyÂ and the Netherlands. It shows the breakthrough of the solution for the development of aÂ commercial market for disabled people, where, for example, in the UK, it can not spend itsÂ budget for the purchase of services other than commercial. In the case of Germany and theÂ Netherlands there is also the professionalization and pulled out of the â€œgray zoneâ€ of care ofÂ family members, neighbors and friends. This is also impacts on the overcoming discriminationÂ against women in the labor market caring, and their work in the care of family members canÂ be rewarded. In the third part of the report the authors present a solution for the mobility of persons withÂ disabilities and commercial services in the field of transport. The best practice is an example ofÂ the UK, which occupies a prominent place in the EU for the provision of commercial servicesÂ for disabled people in the mobility and transport. These are initiatives such as transportÂ cards and vouchers for disabled people, and 100 % adjustment of the commercial fleet forÂ transporting disabled people. The second example is indicated in the statement of Ireland,Â where the challenge is in the continuous adaptation and availability of commercial servicesÂ in the field of mobility, however, there are good practices, such as Vantastic network operatedÂ by a local NGO and providing effective and affordable transportation for the residents ofÂ Dublin. In the fourth part, the authors briefly present the current state of legislation across the boardÂ in terms of electronic availability of television, Internet and other ICT-based services in all EUÂ member states. It also identifies weaknesses in fastest-growing high-tech and mobile phoneÂ industry. In conclusion, the authors provided the recommendations arising from the report, togetherÂ with recommendations for the implementation of commercial services market in Poland.Â Particular attention was devoted to the innovative tool like personal budgets and direction ofÂ change in the approach to services, in which commercial services can be more efficient andÂ more competitive than those provided by public entities.